Volume 2A: Turbomachinery 2016
DOI: 10.1115/gt2016-56891
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Highly Loaded Compressor Airfoils With Active Flow Control Under Non-Steady Flow Conditions in a 3D-Annular Low-Speed Cascade

Abstract: This investigation discusses the impact of a non-steady outflow condition on the compressor stator flow in an annular cascade which is periodically chocked through a rotating disc in the wake, to simulate the expected conditions for a pulsed detonation engine (PDE). A 2D controlled diffusion airfoil of the highly loaded linear stator cascade by [1] has been transferred to the annular compressor test rig to compare results under non-steady conditions via multi-colored oil flow visualization on the suction side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Gbadebo [7] showed that a variation in incidence angle led to changes in size and characteristics of those vortices. As the pitch-to-chord ratio in the annular test rig is smaller on the hub side than at the tip, an asymmetrical occurrence of the corner vortices is observed as shown by Brück [8]. Utilizing different means of flow control has shown that the blade passage losses can be successfully reduced [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gbadebo [7] showed that a variation in incidence angle led to changes in size and characteristics of those vortices. As the pitch-to-chord ratio in the annular test rig is smaller on the hub side than at the tip, an asymmetrical occurrence of the corner vortices is observed as shown by Brück [8]. Utilizing different means of flow control has shown that the blade passage losses can be successfully reduced [9].…”
Section: Introductionmentioning
confidence: 99%
“…The respective positions where c p,T E,a f c has been measured is marked with a red circle in Figure 3. These positions have been chosen because the maximum static pressure at the TE is observed there, as shown in [25,26]. For the actuated case the maximum increase in pressure occurs at the same location.…”
Section: Comparison Of Active Flow Control Resultsmentioning
confidence: 99%
“…low speed, open circuit wind tunnel operated at the flight propulsion laboratory of TUB was used for the annular cascade experiments.Figure 1bshows a schematic depiction of the test section, introduced by Brück et al[21].The diameter of the casing of the test section measures 0.6 m. In order to create an inflow angle to the annular cascade of β 1 = 60 • at midspan 19 variable inlet guide vanes (VIGV s) produce the swirl needed for the stator inlet conditions.…”
mentioning
confidence: 99%
“…Since its radial scale exceeds half-span, more flow will pass through the opposite side at the given inlet Mach number and hence the upper endwall region will not suffer from sever flow separation and passage flow is not symmetric. It is necessary to note that this asymmetric flow phenomenon is a typical flow feature for a highly loaded low aspect ratio annular stator 26 and might also be observed in a planar cascade in some extreme cases. 27 To tell the truth, the outlet aerodynamic parameters distribution in this case is hard to satisfy the engineering applications.…”
Section: Grid Independency Studymentioning
confidence: 96%